2010
DOI: 10.1128/iai.00044-10
|View full text |Cite
|
Sign up to set email alerts
|

Role for Neutrophils in Host Immune Responses and Genetic Factors That Modulate Resistance toSalmonella entericaSerovar Typhimurium in the Inbred Mouse Strain SPRET/Ei

Abstract: Infection with Salmonella enterica serovar Typhimurium is a complex disease in which the host-bacterium interactions are strongly influenced by genetic factors of the host. We demonstrate that SPRET/Ei, an inbred mouse strain derived from Mus spretus, is resistant to S. Typhimurium infections. The kinetics of bacterial proliferation, as well as histological examinations of tissue sections, suggest that SPRET/Ei mice can control bacterial multiplication and spreading despite significant attenuation of the cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…In fact, published studies have shown that mast cells and eosinophils are able to produce IL-4 and modulate granuloma formation in S. mansoni infection [7, 10]. It has also been confirmed that SPRET/EiJ mice show a high level of resistance to infection of other pathogens like Salmonella enterica where macrophages and neutrophils also play a critical role [4]. Previous studies showed that SPRET/EiJ strain is also strongly resistant to inflammation induced either by cytokines or by bacterial products [27].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, published studies have shown that mast cells and eosinophils are able to produce IL-4 and modulate granuloma formation in S. mansoni infection [7, 10]. It has also been confirmed that SPRET/EiJ mice show a high level of resistance to infection of other pathogens like Salmonella enterica where macrophages and neutrophils also play a critical role [4]. Previous studies showed that SPRET/EiJ strain is also strongly resistant to inflammation induced either by cytokines or by bacterial products [27].…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis remains one of the leading causes of death in intensive care units (Vincent et al, 2006) and new therapeutic approaches are urgently needed (Riedemann et al, 2003). We previously showed that SPRET/Ei mice are highly resistant to the lethal effects of LPS (Mahieu et al, 2006), as well as to certain bacterial infections (Dejager et al, 2010a). LPS‐induced lethal inflammation and bacterial infections are often used to study the pathogenesis of sepsis (Dejager et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The great genetic diversity between Mus spretus and Mus musculus has already been instrumental in the identification of genetic loci that contribute to resistance phenotypes of Mus spretus ‐derived strains (Dejager et al, 2009), such as resistance to infection with Salmonella typimurium (Dejager et al, 2010a) and Yersinia pestis (Blanchet et al, 2011). Here, we identified two QTL determining the resistance of SPRET/Ei mice to LPS, one of which is located on the X chromosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published studies have shown that mast cells and eosinophils are able to produce IL-4 and modulate granuloma formation (Gessner, et al, 2005. In addition, it has also been demonstrated that SPRET/Ei mice showed a high level of resistance to 6 infection of other pathogens, like Salmonella enterica, where macrophages and neutrophils play a critical role in controlling invading pathogens in the periphery by phagocytosis and the production of antimicrobial proteins (Dejager, et al, 2010). Furthermore, previous studies showed that SPRET/Ei is also strongly resistant to inflammation induced either by cytokines or by bacterial products (Turcotte, et al, 2006).…”
Section: Discussionmentioning
confidence: 99%